Impact Of Foreign Investment On Infrastusture Connections In Countries (Malaysia, Nigeria, India) - Aina Shofi Kumala (Journal of Economic and Business Analysis, 2024)
Abstrac : This study aims to analyze the effects of global interest rates, global commodity prices, and global stock markets on access to electricity in developing countries during the period 2018–2022. Using a quantitative approach with panel data analysis, this study finds that global interest rates have a significant effect on electricity access, with a negative coefficient indicating that an increase in global interest rates can reduce electricity access. In contrast, global commodity prices do not show a significant effect on electricity access, while the global stock market has an effect that is close to significant. These findings indicate that global economic uncertainty, as reflected in changes in interest rates and stock markets, can worsen electricity infrastructure financing, especially in developing countries that rely on foreign investment. This study uses secondary data from international and national sources and analysis using STATA 17 software with classical assumption tests and panel data regression. The results of this study provide insight into the importance of considering global economic factors in planning electricity access development policies. Keywords : Electricity Access, Global Interest Rates, Global Commodity Prices, Global Stock Markets, Developing Countries, Panel Data Analysis.